2013
DOI: 10.1109/tnano.2013.2273805
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Threshold Voltage Model for Triple-Material Cylindrical Gate-All-Around (TM-CGAA) MOSFETs

Abstract: In this paper, an analytical threshold voltage model is proposed for a triple-material cylindrical gate-all-around MOSFET considering parabolic approximation of the potential along the radial axis. The center (axial) and the surface potential models are obtained by solving the 2-D Poisson's equation in the cylindrical coordinate system. This paper refutes the estimation of the natural length using surface potential as in previous work and proposes the use of center-potential-based natural length formulation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…The surface potential along the z-axis φ s (z) is related to the center potential φ c (z) as follows [24]:…”
Section: Center Potential Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface potential along the z-axis φ s (z) is related to the center potential φ c (z) as follows [24]:…”
Section: Center Potential Formulationmentioning
confidence: 99%
“…All of the above discussed TFET models employ a 2-D analytical solution of the Poisson equation based on surface potential. However, Dubey et al [24] developed an analytical model for CG-MOS based on potential at the center of the cylindrical body. They reported that the characteristic length of the center potential model is smaller compared to the conventional surface potential-based model.…”
Section: Introductionmentioning
confidence: 99%
“…The Cylindrical Gate all around (CGAA) MOSFET architecture [5][6], the channel is surrounded by the gate so that the gate has more control over the channel which further minimizes the SCEs. Because of the shorter dimension and higher drive current, CGAA MOSFETs can achieve higher packing density as compared to double gate (DG) MOSFETs [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, it has been observed that solving the center potential in the channel may produce more accurate results as compared to surface potential [12]. To solve the Poisson's equation, an assumption is made as the potential inside the channel has parabolic nature [13].…”
Section: Introductionmentioning
confidence: 99%